Impact of nutrition training on long-term adoption of high-zinc rice: A randomized control trial study among female farmers in Bangladesh - Valera, Harold Glenn; Yamano, Takashi; Pede, Valerien; Puskur, Ranjitha; Habib, Muhammad Ashraful; Bashar, Md. Khairul (International Association of Agricultural Economists, 2021)
Lack of understanding of the need for micronutrients among farmers is a major constraint on the adoption of biofortified crops. To examine the issue, we conducted a micro-nutrition training among female farmers with young children in randomly selected villages of Bangladesh in May–June 2017. One week after the training, we conducted a phone-based bidding on high-zinc rice seeds among trainees and their counterparts in control villages. If the bidding price was higher than a pre-fixed price, the bidders were asked to buy a 2.5-kilogram bag at the pre-fixed price. More than 70% of the treated female farmers participated in the bidding process and only 23% were from the control group. Female farmers who self-proclaim to be actively involved in decision-making bid a higher price than other female farmers. To measure the long-term impact of the training, we conducted follow-up surveys in 2018, 2019, and 2020 and found that the adoption of high-zinc rice in Aman season declined from 59% in 2018 to 7.5% in 2020 among treated farmers and from 12.9% to 1.9% among control farmers. The regression analysis indicates that nutrition training has a long-term but diminishing impact on the adoption of high-zinc rice. Among treatment farmers, unavailability of seeds and low yields were cited as major reasons for not using high-zinc rice, while lack of knowledge about high-zinc rice was a dominant reason among control farmers.